The Effect of Rhythmic Movement Activities Using Sticks on Students’ Flexibility - M. Adit Alfayat; Recky Ahmad Haffiyandi; Mita Erliana; Eka Purnama Indah (Jurnal Master Penjas & Olahraga, 2026)
Flexibility is an important component of physical fitness that supports movement efficiency and injury prevention. This study aimed to determine the effect of rhythmic movement activities using sticks on students’ flexibility. A quantitative pre-experimental method with a one-group pretest–posttest design was employed. The sample consisted of 33 ninth-grade students selected through purposive sampling. Flexibility was measured using the Shoulder Flexibility Test before and after the intervention. Data were analyzed using descriptive statistics, a normality test, and a paired-samples t-test at a significance level of 0.05. The results showed an improvement in flexibility, with the mean score decreasing from 25.27 cm in the pretest to 16.24 cm in the posttest. The paired-samples t-test yielded a t-value of 14.103 and a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. Therefore, rhythmic movement activities using sticks effectively improve students’ flexibility.